Lightning Surge Response of Concrete Pole due to Effect of the Electrical Properties of Concrete based on the Electromagnetic Field Method - Samroeng Hintamai; Jamnarn Hokierti (Agriculture and Natural Resources, 2005)
Lightning performance of overhead distribution line affects the cost of line construction. For economical insulation coordination in distribution line design, it is necessary to accurately predict the lightning surge overvoltage that occurs in the electric power system. In particularly, tower or pole surge impedance is one of the most important parameters for lightning surge analysis of distribution lines. This paper presents the lightning surge response of reinforced concrete pole due to the electrical properties of concrete based on the electromagnetic field theory, which has never been considered in the previous lightning surge analysis. The electrical properties of concrete were measured over the frequency of range from 100 Hz to 40 MHz during 86 days after pouring. The concrete sample was mixed according to a construction standard of the electrical distribution pole of Provincial Electricity Authority (PEA). The cement/sand/aggregate ratio was about 1:1.5:3 and water/cement ratio was approximately 0.3. It was found that the electrical properties of concrete varied significantly over the frequencies and time after pouring. Therefore, lightning surge response of reinforced concrete pole depended on the electrical properties of concrete. The results showed that surge impedance calculated by the proposed formula agreed well with the other measured value obtained from reduced- scale test.